On the textual basis of Old Prussian Enchiridion used by Nesselmann (1845) and his successors Uhlenbeck (1889) and Berneker (1896) - U. Dini, Pietro (Baltistica, 2021)
In the middle of the 19th century, G. H. F. Nesselmann’s Die Sprache der alten Preußen an ihren Überresten erläutert (Königsberg, 1845) presented all the available knowledge on the OPr. language at that time. Specifically, Nesselmann’s information on the philological tradition of the third Catechism, the so-called Enchiridion, showed a great progress compared to his predecessors and was considered a reference work until Trautmann’s Die altpreußischen Sprachdenkmäler (1910). Footnote 2 in Nesselmann’s edition is however enigmatic: it gives an insight on his use of the three copies of the Enchiridion that he firstly knew. Furthermore, it is also taken into consideration how the other two editors of the Enchiridion, Uhlenbeck and Berneker, in the 19th century understood Footnote 2 and the problems it involved.